2012
DOI: 10.1016/j.stem.2012.09.014
|View full text |Cite
|
Sign up to set email alerts
|

p27Kip1 Directly Represses Sox2 during Embryonic Stem Cell Differentiation

Abstract: SummaryThe mechanisms responsible for the transcriptional silencing of pluripotency genes in differentiated cells are poorly understood. We have observed that cells lacking the tumor suppressor p27 can be reprogrammed into induced pluripotent stem cells (iPSCs) in the absence of ectopic Sox2. Interestingly, cells and tissues from p27 null mice, including brain, lung, and retina, present an elevated basal expression of Sox2, suggesting that p27 contributes to the repression of Sox2. Furthermore, p27 null iPSCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
157
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(170 citation statements)
references
References 36 publications
(59 reference statements)
8
157
0
3
Order By: Relevance
“…Recent studies have shown that p27 plays other essential roles in the regulation of cell differentiation and apoptosis (Liu et al, 2010;Li et al, 2012b).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that p27 plays other essential roles in the regulation of cell differentiation and apoptosis (Liu et al, 2010;Li et al, 2012b).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of Cdk phosphorylation on MyoD can similarly be counteracted by association with p57, which in turn promotes the accumulation of MyoD and the transactivation of muscle-specific genes (Reynaud et al, 2000). Two separate studies have recently shown that the binding of p21 and p27 to the enhancer of Sox2, which encodes an HMG-box transcription factor essential for the maintenance of stem cell identity, is key to its transcriptional silencing so that differentiation can be initiated in NSCs and ESCs (Li et al, 2012a;Marqués-Torrejón et al, 2013). Taking into consideration the extensive involvement of Cdks, cyclins and CKIs in the specification of cell fate (Fig.…”
Section: Cdks Cyclins and Ckis Regulating Metabolismmentioning
confidence: 99%
“…More recently, Sox2 was revealed by overexpression experiments in genetically engineered mouse models to be a driver of lung SCC 13 . Sox2 was also shown to be critical for the initiation of pituitary gland tumors upon loss of the tumor suppressor p27 or of the retinoblastoma tumor suppressor gene Rb 14,15 . Similarly, Sox2 was required for tumor initiation by murine oligodendroglioma cells and by human glioblastoma cells transplanted into appropriate mouse model systems, in agreement with the reported role of Sox2 in maintaining glioma-initiating cells [16][17][18] .…”
Section: Introductionmentioning
confidence: 99%